Proteomics of Maize Root Development - Hochholdinger, Frank; Marcon, Caroline; Baldauf, Jutta A.; Yu, Peng; Frey, Felix P. (Frontiers in Plant Science, 2018)
Maize forms a complex root system with structurally and functionally diverse root types that are formed at different developmental stages to extract water and mineral nutrients from soil. In recent years proteomics has been intensively applied to identify proteins involved in shaping the three-dimensional architecture and regulating the function of the maize root system. With the help of developmental mutants, proteomic changes during the initiation and emergence of shoot-borne, lateral and seminal roots have been examined. Furthermore, root hairs were surveyed to understand the proteomic changes during the elongation of these single cell type structures. In addition, primary roots have been used to study developmental changes of the proteome but also to investigate the proteomes of distinct tissues such as the meristematic zone, the elongation zone as well as stele and cortex of the differentiation zone. Moreover, subcellular fractions of the primary root including cell walls, plasma membranes and secreted mucilage have been analyzed. Finally, the superior vigor of hybrid seedling roots compared to their parental inbred lines was studied on the proteome level. In summary, these studies provide novel insights into the complex proteomic interactions of the elaborate maize root system during development.